2021
DOI: 10.1055/s-0041-1730971
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange in Acute and Acute on Chronic Liver Failure

Abstract: Liver failure in the context of acute (ALF) and acute on chronic liver failure (ACLF) is associated with high mortality in the absence of a liver transplant. For decades, therapeutic plasma exchange (TPE) is performed for the management of immune-mediated diseases. TPE has emerged as an attractive extracorporeal blood purification technique in patients with ALF and ACLF. The basic premise of using TPE is to remove the toxic substances which would allow recovery of native liver functions by facilitating liver r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 166 publications
(212 reference statements)
0
34
0
Order By: Relevance
“…In contrast, other artificial support systems did not reach statistical significance in this meta-analysis (51). Overall, several studies have indicated that PE might be a feasible treatment strategy in ACLF (52,53). However, due to the low quality of evidence, larger RCTs are required, which are currently undertaken, for example by the APACHE trial.…”
Section: Management Of Aclf Before Ltmentioning
confidence: 79%
“…In contrast, other artificial support systems did not reach statistical significance in this meta-analysis (51). Overall, several studies have indicated that PE might be a feasible treatment strategy in ACLF (52,53). However, due to the low quality of evidence, larger RCTs are required, which are currently undertaken, for example by the APACHE trial.…”
Section: Management Of Aclf Before Ltmentioning
confidence: 79%
“… 91 Therapeutic plasma exchange would allow recovery of native liver function by facilitating liver regeneration through reducing systemic inflammatory mediators and removing toxic substances. Studies related to therapeutic plasma exchange have shown improvement in systemic hemodynamics and encephalopathy in patients with ACLF, 92 but none of these studies have assessed renal function improvement specifically in patents with HRS-AKI.…”
Section: Treatment Of Hrsmentioning
confidence: 99%
“… Source: Adapted and modified from Maiwall and Sarin. 92 AKI: acute kidney injury; CKD, chronic kidney disease; Cr Cl, creatinine clearance; eGFR, estimated glomerular filtration rate; ESRD, end-stage renal disease; HUS, hemolytic uremic syndrome; OPTN, Organ Procurement and Transplantation Network; SLK, simultaneous liver–kidney; SLKT, simultaneous liver–kidney transplant. …”
Section: Treatment Of Hrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma exchange can be performed either by membrane separation or centrifugal separation. Systemic heparin anticoagulation membrane TPE is a common TPE treatment method in patients with liver failure [2]. In recent years, regional citrate anticoagulation (RCA) has become a favorable alternative to heparin in patients at risk from excessive bleeding.…”
mentioning
confidence: 99%